Exploring mental health literacy among youths with background as asylum-seekers and refugees: a systematic review - Sandsgård-Hilmarsen, Eli; Ree, Eline; Salamonsen, Anita; Viksveen, Petter (Frontiers in Psychiatry, 2025)
The purpose of this study was to explore mental health literacy among youths with a background as asylum-seekers and refugees including the role of mental health literacy as a barrier to their service use. A systematic literature study was conducted to gain an overview of mental health literacy in youths with a background as asylum-seekers and refugees. The databases MEDLINE, PubMed, CINAHL, PsycINFO and Web of Science were used to identify relevant research. The PRISMA statement was used to report on the literature search, and a thematic synthesis was used to analyze the data from the included studies. Eleven studies reporting qualitative data were included. The understanding of mental health varied. Some youths understood mental health and mental health problems as connected to body and mind, whereas others linked it to their life situation or attributed it to supernatural or religious causes. Help-seeking behavior also varied, with youths seeking support in ways they found helpful, such as through prayer, or talking to an Imam or priest, or confiding in friends and family. Professionals were often perceived as unhelpful, partly due to lack of cultural competency. Youths expressed mistrust of professionals, feeling that they focused too much on their past rather than addressing their present and future concerns. Moreover, mental health stigma was a significant barrier to seeking help. Different understandings of mental health among youths with a background as asylum-seekers and refugees influence their help-seeking behaviors. The current conceptual framework of mental health literacy does not address cultural and contextual factors. Mental health literacy should be further developed as a concept to encompass diverse perspectives. Professionals should be trained with a more holistic approach that considers cultural factors and user experiences, guiding the development of mental health literacy programs and services.